Integrated Reporting Implementation in the Health Sector Industry - Dini Wahjoe Hapsari; Khalisha Azzahra Khairunnisa (Australasian Accounting, Business and Finance Journal, 2023)
Integrated reporting is an organization's process of communicating information to stakeholders about value creation from time to time. This report provides material details on an organization's strategy, governance and compensation, achievement, risk, and prospects, as well as the business, social, and environmental context in which it operates. The output of integrated reporting is an integrated report which is the main report of the organization. This study aims to determine the extent to of health sector companies listed on IDX respond to integrated reporting as a future corporate reporting trend. The information was gleaned from annual reports of health firms determined using purposive sampling of 60. To test the hypothesis developed using Partial Least Square-Structural Equation Modelling (PLS-SEM). The findings showed that institutional ownership, managerial ownership, and gender diversity are positively related to integrated reporting. This research can be helpful for policymakers and other regulators for impactful frameworks on integrated reporting.
Keywords: Institutional ownership; Managerial ownership; Gender diversity; Integrated reporting